(untitled) (Research, Society and Development, 2025)
Industrial sectors, in partnership with universities, have studied abrasive wear. This study aims to analyze the action of wear on equipment surfaces, by measuring parameters such as area, diameter, and worn volume, resulting in the determination of the wear coefficient. Experimental laboratory research was carried out, in which three abrasive minerals were used: gneiss, iron ore waste, and silicon carbide. The materials underwent comminution and sieving, collecting the 400-mash pass-through. The wear tests were carried out on ASTM A-36 steel specimens, prepared at the Technological Center (CTec) of the State University of Minas Gerais, João Monlevade campus (UEMG-João Monlevade). Four wear tests were defined, with sliding distances: 25, 50, and 100 meters. The equipment used combined normal force with load C to evaluate abrasive wear. During the tests, the abrasive slurries were applied drop by drop to the contact area between the test specimens and the fixed sphere. The results showed that iron ore waste and gneiss showed increasing variation in wear coefficient, with different rates. There was an increase in the wear coefficient in silicon carbide tests, but in the last test, there was a reduction. This study demonstrates the feasibility of the equipment developed to simulate abrasive wear, providing important data on the factors that influence wear and the achievement of a permanent wear regime.